North American Free Trade Agreement : green law or green spin? - CHARNOVITZ, Steve (1994)
Explains the rules of the GATT, as they relate to the environment, in order to provide a baseline for judging the significance of the NAFTA. Examines some of the environmental claims made by proponents of NAFTA, and compares them to the actual terms of the Agreement. Concludes that on the one hand, economic development and trade can be consistent with a healthy environment if the proper environmental policies are in place. Since proper policies are not in place in the three NAFTA member states, and since the North American Agreement on Environmental Cooperation does little to remedy this, there are grounds for concern. On the other hand, a free trade agreement can raise income in all three countries and therefore make them more able to afford environmental protection. Trade liberalization can also lead to a more efficient use of natural resources. But the critical factor will be the political will of each of the governments to undertake reforms.